(untitled) (Research, Society and Development, 2021)
The aim of this study was to describe the diversity and prevalence of gastrointestinal parasites in dogs from the three biomes in central Brazil between 2019 to 2020. In this study, we analyzed fecal samples from dogs using spontaneous sedimentation tests and centrifugal fluctuation in sucrose. Prevalence percentages were calculated with 95% confidence intervals, chi-square test to assess significant differences and Shannon index to calculate species diversity and equitability. After analyzing 130 fecal samples, the prevalence of intestinal parasites was 57% Helminths were found in 84% of the samples and protozoa in 71%. There was no statistically significant difference between the prevalence of the studied biomes. Shannon’s diversity and evenness indices were similar in the three biomes. The proportion of co-infection was 65%, and single infections 35%. In this study, we observed a high prevalence of gastrointestinal parasites in dogs from the three biomes that make up the central region of Brazil. The index of diversity and equitability of gastrointestinal parasites was similar in the three biomes analyzed, revealing the presence of 12 species of parasites, being Blastocystis sp., Giardia sp. and Entamoeba coli the most prevalent protozoa and among the helminths Ancilostomídeos, Toxocara sp. and Trichuris sp. We can conclude that routine epidemiological surveillance, effective veterinary care and improved educational campaigns on parasitic zoonoses in dogs, are essential measures to minimize environmental contamination, prevent the transmission of parasites to other animal hosts and reduce the risks to public health in the biomes of the central region of Brazil.